2021
DOI: 10.1371/journal.pone.0246178
|View full text |Cite
|
Sign up to set email alerts
|

Size, not temperature, drives cyclopoid copepod predation of invasive mosquito larvae

Abstract: During range expansion, invasive species can experience new thermal regimes. Differences between the thermal performance of local and invasive species can alter species interactions, including predator-prey interactions. The Asian tiger mosquito, Aedes albopictus, is a known vector of several viral diseases of public health importance. It has successfully invaded many regions across the globe and currently threatens to invade regions of the UK where conditions would support seasonal activity. We assessed the f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 60 publications
3
16
1
Order By: Relevance
“…Previous work showed that M. viridis exhibits a type II functional response curve and a relatively high predation efficiency against Ae. albopictus prey at temperatures representative of UK larval habitats [50]. This study builds on recent work and further supports the use of M. viridis as a biocontrol agent for Ae.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Previous work showed that M. viridis exhibits a type II functional response curve and a relatively high predation efficiency against Ae. albopictus prey at temperatures representative of UK larval habitats [50]. This study builds on recent work and further supports the use of M. viridis as a biocontrol agent for Ae.…”
Section: Discussionsupporting
confidence: 78%
“…Due to the suitability of some areas in South East England for Ae. albopictus populations [49], we used Megacyclops viridis, a likely copepod species for future biocontrol applications [50], collected from Longside Lake in Egham, UK, and Ae. albopictus that were originally collected in Montpellier, France.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that M. viridis exhibits a type II functional response curve and a relatively high predation efficiency against Ae. albopictus prey at temperatures representative of UK larval habitats [49]. This study builds on recent work and further supports the use of M. viridis as a biocontrol agent for Ae.…”
Section: Discussionsupporting
confidence: 77%
“…Due to the suitability of some areas in southeast England for Ae. albopictus populations [48], we used Megacyclops viridis , a likely copepod species for future biocontrol applications [49], collected from Longside Lake in Egham, UK, and Ae. albopictus that were originally collected in Montpellier, France.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the lower density of females at high temperatures may free up males and juveniles to forage at high temperatures. Our results on the temperature dependence of space clearance rates contrast with experimental examinations of temperature effects on functional responses in which individuals are often exposed to a uniform temperature and are typically in homogeneous arenas with no potential temperature refuges (Archer et al, 2019;Broom et al, 2021;Islam et al, 2021;Russell et al, 2021) This difference has potentially strong implications for the general way in which we conceive of temperature altering predator-prey interactions and thus food web dynamics given changing climates. Using more realistic temperature regimes and arenas in experiments will allow us to understand whether our result is unique to zebra jumping spiders or potentially more widespread in terrestrial ectotherms.…”
Section: Discussioncontrasting
confidence: 61%